APOBEC3A is an oral cancer prognostic biomarker in Taiwanese carriers of an APOBEC deletion polymorphism - Ting-Wen Chen (Nature Portfolio, 2017)
Oral squamous cell carcinoma is a prevalent malignancy in Taiwan. Here, the authors show that OSCC in Taiwanese show a frequent deletion polymorphism in the cytidine deaminases gene cluster APOBEC3 resulting in increased expression of A3A, which is shown to be of clinical prognostic relevance.